Aplicação da competência em informação no contexto escolar: uma experiência no Colégio Militar de Campo Grande - MS - Pereira, Rodrigo [UNESP] (2010)
The research presents the Information Literacy and its development as a part of the educational processes related to the reflexive, critical and autonomous formation. It is linked to the School Culture, through which becomes evident the causes and effects that make difficult the planning of programs which develop the Information Literacy. As main goal, we tried to evaluate an Information Literacy program based on Carol Kuhlthau´s work, (2004),developed by the Military School of Campo Grande – MS. The specific objectives are: a) present the development of Information Literacy in the context of the College; b) externalizing the results of the program based on the work of Carol Kuhlthau; c) make sure the validity of the portfolio as a methodological procedure for the evaluation Information Literacy; d) assess the possible development of research subjects with respect access, use and production of knowledge. Evaluation methods are analyzed aiming at the identification of the best practices and procedures which support the evaluative process of the Information Literacy .The actionresearch was used , having as research environment the school above mentioned and as subject-matter of the research, 20 students from the sixth and seventh years from which,8 entered the school through a public selection process and 12 are supported for being children of military personnel on active duty. As a research tool, we decided to use a questionnaire aiming at the identification of the Information Literacy level of the group which was being analised, the group took part of a program to the Information Literacy development .As a result of the program, portfolios were structured during the development of the activities proposed to the group through which it was possible to evaluate the abilities and attitudes inherent to the Information Literacy. The portfolios were constituted by an applied questionnaire... (Complete abstract click electronic access below)